Reporting on Science as an Ongoing Process (or Not) - Slater, Matthew H.; Scholfield, Emily R.; Moore, J. Conor (Frontiers in Communication, 2021)
Efforts to cultivate scientific literacy in the public are often aimed at enabling people to make more informed decisions — both in their own lives (e.g., personal health, sustainable practices, &c.) and in the public sphere. Implicit in such efforts is the cultivation of some measure of trust of science. To what extent does science reporting in mainstream newspapers contribute to these goals? Is what is reported likely to improve the public’s understanding of science as a process for generating reliable knowledge? What are its likely effects on public trust of science? In this paper, we describe a content analysis of 163 instances of science reporting in three prominent newspapers across three years in the last decade. The dominant focus, we found, was on particular outcomes of cutting-edge science; it was comparatively rare for articles to attend to the methodology or the social–institutional processes by which particular results come about. At best, we argue that this represents a missed opportunity.